2015
DOI: 10.1002/acp.3118
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Differences in the Ability to Provide Temporal Information About Repeated Events

Abstract: . (2015). Developmental differences in the ability to provide temporal information associated with an instance of a repeated event. Applied Cognitive Psychology, 29,[407][408][409][410][411][412][413][414][415][416][417] We are grateful to the children, parents and schools who participated, and to the numerous TEMPORAL MEMORY OF A REPEATED EVENT 3 AbstractChildren (n = 372) aged 4 -8 years participated in 1 or 4 occurrences of a similar event and were interviewed 1 week later. Compared to 85% of children who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
(95 reference statements)
2
22
0
Order By: Relevance
“…Importantly, old low‐performing children exhibited an intermediate performance, making many more temporal resolution errors than old high‐performing children. Our findings are thus consistent with those of (Roberts et al, ) concerning the impairments that young children have in forming clear memory representations of repeated events, but further suggest that these difficulties arise during encoding or the earliest stages of consolidation, as our task's intertrial interval was a few minutes rather than hours or days.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, old low‐performing children exhibited an intermediate performance, making many more temporal resolution errors than old high‐performing children. Our findings are thus consistent with those of (Roberts et al, ) concerning the impairments that young children have in forming clear memory representations of repeated events, but further suggest that these difficulties arise during encoding or the earliest stages of consolidation, as our task's intertrial interval was a few minutes rather than hours or days.…”
Section: Discussionsupporting
confidence: 92%
“…There is a relatively large literature concerning the temporal coding of children's event memories. Briefly, whereas children as young as 4 years of age are capable of distinguishing between relatively recent and less recent events (i.e., making temporal distance judgments (Friedman, )), children even up to 8 years of age have difficulty in temporally sequencing individual instances of a repeated event (compared to one‐time events (Roberts et al, )). Nevertheless, and similar to spatial memory, children's temporal coding of unique events improves between 3 and 8 years of age (Drummey & Newcombe, ; Hayne & Imuta, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that most of the minimally verbal adults in our sample would be able to respond to the "one time or more than one time" question. Roberts et al (2015) found that none of the 4-to 8-year-old children in their analogue study answered it incorrectly (even though they made mistakes in response to the cued recall question about the precise number of times).…”
Section: Talking About Occurrences Of Repeated Eventsmentioning
confidence: 92%
“…Children participated in a 25‐min scripted activity session (the Deakin Activities) on four occasions. Each episode comprised 16 target items administered in a fixed temporal order and centred around six main activities: meeting a puppet, listening to a story, doing a puzzle, relaxing, getting refreshed, and receiving a surprise (see Powell & Thomson, ; Roberts et al ., ). In each episode of the Deakin Activities, the specific presentation of the memory items (i.e., the instantiation of the item) varied according to a schedule, so that each individual episode was somewhat different.…”
Section: Methodsmentioning
confidence: 99%